The Surprising Role of Endogenous Calcium Carbonate in Crab Shell-Mediated Biosorption of Pb (II) - Carolina Londoño-Zuluaga; Hasan Jameel; Ronalds W. Gonzalez; Guihua Yang; Lucian Lucia (Physchem, 2024)
Crustacean shells, waste from the seafood industry, have been identified as a potential sustainable material for the adsorption of lead, a potent heavy metal found in the discharge of industrial processes. The dynamics and kinetics of its performance were evaluated in batch experiments under pH, temperature, time, and initial concentration. A unique and non-intuitive key finding was that among the native components of the crab shell matrix, i.e., chitin, protein, and calcium carbonate, calcium carbonate was instrumental in sequestration. The role of protein was minimal, whereas the efficiency of chitin in lead complexation was linked to the lead atomic radius, which, of the crab shell components, we determined was very prone to interacting with chitin.